A Monetary Equilibrium with the Lender of Last Resort - Tarishi Matsuoka; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the role of a lender of last resort (LLR) in a monetary model where a shortage of a bank's monetary reserves (a liquidity crisis) occurs endogenously. We show that discount window lending by the LLR is welfare-improving but reduces banks' ex-ante incentive to hold monetary reserves, which increases the probability of a liquidity crisis, and can cause moral hazard in capital investment. We also analyze the combined effects of monetary and extensive LLR policies, such as a nominal interest rate, a lending rate, and a haircut.
Keywords: E40; 330; monetary equilibrium; liquidity crisis; lender of last resort; moral hazard